ENHANCING INMATE MEETING PROCESSES: A SIMULATION-DRIVEN BUSINESS PROCESS ENGINEERING APPROACH - Reema Choudhary; Adrees Shahbaz; Ali Usman; Nauman Riaz Chaudhry; Muhammad Hanan Haider; Muhammad Suhail (International Journal of Contemporary Issues in Social Sciences, 2024)
In this era everyone prefers smart work than the hard work that takes too many resources and the time in contradiction they like efficient ways to run their work. Business Process Engineering (BPE) is a way which provide the efficiency and authentication for your business process and help to make changes, improve productivity and make you able to calculate the operational cost. We apply the business process engineering in inmate meeting system of the Central Jail of a City. We did the survey and found that there are many people who come to meet their beloved ones in the Central Jail. It will create a crowd of people outside the Jail Gate and then people must wait in the multiple queues which is very time consuming and inconvenience for the people. We consider this process as our current business and make improvement in it by introducing the online system that will eliminate queue system in token area and reduce the waiting time in waiting room. We looked up at the problem by making its simulation model. The Solution simulation model is prepared for it and check it properly. This will solve the problem, provide the clear way of implementation and require less number of resources.